Evaluación de la oferta y demanda del recurso hídrico - propuesta de mejoras para el sistema de acueducto de San Isidro de El Guarco, Cartago, Costa Rica - Ureña-Vargas, Laura Vanesa (Instituto Tecnológico de Costa Rica, 2016)
The Aqueduct Administration Association (ASADA, according to initials in Spanish) in San Isidro, El Guarco, has shown problems with the administration, operation and maintenance of the aqueduct, which have not allowed it to provide a permanent, continuous, sufficient and equalitarian service of potable water supply to the target population. This leads to set the study of the quality and quantity of the available water resource, assessing whether this is enough to supply the current and future population. Also, were evaluated taking into account the components of the water system (intake structures, pretreatment, conduction, water treatment system and disinfection) and the management of the ASADA in providing the service. The process required the analysis of the available data; either files, field visits, flow measurement, sampling water, physical-chemical and microbiological analysis, georeferencing of structures, determination of current and future consumption of drinkable water, in addition there was an evaluation of the components of the aqueduct, in order to establish the present risks and the design of the pretreatment, purification and storage system. As a result, a variation in the available flows rates was found, without an apparent link between these and the rainfall, it was determined a consumption of 180 liters of water per person per day, with a variation in the demand for potable water of 5.2 L/s in 2015 to 20.03 L/s in 2030. It also was determined that, with the fluctuation of the water level sources, the water supply in the future cannot be guaranteed. A redesign of the current treatment system is also indispensable, that is why I proposed a Multi-Stage Filtration (MSF) technology, with improvements in the intake structures, the disinfection and the storage structures.
Proyecto de Graduación (Licenciatura en Ingeniería Ambietal) Instituto Tecnológico de Costa Rica, Escuela de Química, 2016.
Keywords: Recurso hídrico; FiME; ASADA; Agua potable; Mantenimiento preventivo